Meningkatkan kompetensi guru bimbingan dan konseling melalui pelatihan pengembangan psikotes - Widodo, Wahyu; Nur Eva; Laila Indra Lestari; Rizka Fibria Nugrahani; Shokhwatunnisa; Indah Wahyuningrum (Global Action and Education for Society, 2025)
This study describes a training program designed to enhance the competence of Guidance and Counseling (BK) teachers in developing psychological measurement instruments within the MGBK Junior High Schools of Trenggalek Regency. The training adopted a quantitative approach with an instrument development design, focusing on improving teachers’ conceptual understanding and technical skills in constructing, validating, and analyzing psychological scales. The program consisted of pre-test and post-test assessments, workshops, group assignments, and evaluation surveys. Results indicated a significant improvement in participants’ competencies, with an average increase of 54.1%, particularly in applying psychometric analysis software. Five groups successfully produced reliable and contextually relevant psychological scales, with Cronbach’s alpha ranging from 0.74 to 0.88. Survey data also showed a high satisfaction rate (91.1%) among participants, emphasizing the relevance and practicality of the training. The findings suggest that experiential, practice-based training supported by university–school collaboration effectively strengthens teachers’ psychometric literacy and promotes evidence-based counseling practices. Future studies are recommended to conduct confirmatory factor analysis (CFA) and wider trials to enhance the validity and applicability of the developed instruments